The Mental Activity and eXercise (MAX) trial: a randomized controlled trial to enhance cognitive function in older adults - Barnes, Deborah E; Santos-Modesitt, Wendy; Poelke, Gina; Kramer, Arthur F; Castro, Cynthia; Middleton, Laura E; Yaffe, Kristine (JAMA internal medicine, 2013)
The prevalence of cognitive impairment and dementia are projected to rise dramatically during the next 40 years, and strategies for maintaining cognitive function with age are critically needed. Physical or mental activity alone result in relatively small, domain-specific improvements in cognitive function in older adults; combined interventions may have more global effects. To examine the combined effects of physical plus mental activity on cognitive function in older adults. Randomized controlled trial with a factorial design. San Francisco, California. A total of 126 inactive, community-residing older adults with cognitive complaints. All participants engaged in home-based mental activity (1 h/d, 3 d/wk) plus class-based physical activity (1 h/d, 3 d/wk) for 12 weeks and were randomized to either mental activity intervention (MA-I; intensive computer) or mental activity control (MA-C; educational DVDs) plus exercise intervention (EX-I; aerobic) or exercise control (EX-C; stretching and toning); a 2 × 2 factorial design was used so that there were 4 groups: MA-I/EX-I, MA-I/EX-C, MA-C/EX-1, and MA-C/EX-C. Global cognitive change based on a comprehensive neuropsychological test battery. Participants had a mean age of 73.4 years; 62.7% were women, and 34.9% were Hispanic or nonwhite. There were no significant differences between the groups at baseline. Global cognitive scores improved significantly over time (mean, 0.16 SD; P < .001) but did not differ between groups in the comparison between MA-I and MA-C (ignoring exercise, P = .17), the comparison between EX-I and EX-C (ignoring mental activity, P = .74), or across all 4 randomization groups (P = .26). In inactive older adults with cognitive complaints, 12 weeks of physical plus mental activity was associated with significant improvements in global cognitive function with no evidence of difference between intervention and active control groups. These findings may reflect practice effects or may suggest that the amount of activity is more important than the type in this subject population. clinicaltrials.gov Identifier: NCT00522899.